APAKAH LIFESTYLE AIO, PERCEIVED USEFULNESS DAN PERCEIVED EASE MEMPENGARUHI INTENTION TO USE DARI TIX ID - Alberta Ines Novenia; Lina Salim (STIE Pelita Nusantara Semarang, 2021)
The purpose of this study was to analyze the influence of lifestyle AIO, perceived usefulness and perceived ease of use on intention to use both directly and with the moderation of age, gender and income. The total number of hypotheses proposed is 12. The research model consists of three independent variables, three moderating variables and one dependent variable. Respondents in this study were people who love watching at cinema aged 16-35 years in Jakarta and Tangerang and have never used TIX ID. This research was conducted by distributing questionnaire to 430 respondents from people who loves watching at cinema in Jakarta and Tangerang and had never purchased movie tickets using TIX ID before. The total number of hypotheses proposed is 12. Three hypotheses have directly influenced intention to use significantly while eight hypotheses have no significant effect. The research model has been tested based on SPSS macros. The results of the study show that lifestyle AIO, perceived usefulness and perceived ease of use directly influence intention to use. On the other hand, moderating variable age, gender and income does not affect the relationship between independent variables with dependent variables